ASAS PROPORSIONALITAS DALAM PEMBAYARAN GANTI RUGI MELALUI ASURANSI DALAM KASUS MALPRAKTIK DOKTER - Putri, Ni Putu Ayu Myra Gerhana (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
In a malpractice medical insurance context, indemnity obligations of malpractice, particularly for improper practice performed by medical team, currently only based on overall team fault, means every physician in the team should bear the compensation evenly. This scheme is not fair because the physician who did lower degree of mistakes must bear the compensation as great as the physician with higher degree of mistakes. That is why proporsional concept, based on the degree of the mistakes, for indemnity obligations needs to be considered. However, this scheme will need some instruments that can align the responsibility among the physician in the team. This instrument then can be used as a basis for determining the degree of mistakes and further the level of compensation the physician need to bear with. This research is a normative legal research and using a statue approach, means legislation as the primary legal materials. In addition, this research also uses books, articles, and materials from the Internet, as well as direct interview with the competent parties as a secunder data. The results showed that because there are no rules governing the law of proporsionality in the legislation make the degree of mistakes is not used as basis for determining the compensation’s level. In fact there are instruments that can be used as basis to determine the degree of mistakes such as Standard Operational Procedure (SOP) and Medical Professional Standard. It is clear that the healthcare legislation should include provisions that govern the determination of the compensation by using proportional approach, in order to align the responsibility among the parties
Keywords: Malpractice; Compensation/Indemnity; Insurance